Bimodal coarse-grained and unimodal ultrafine-grained biodegradable Zn-0.5Mn alloy: Superplastic mechanism and short-term biocompatibility in vivo. (June 2022) - Guo, Pushan; Ren, Tiantian; Liu, Yaxuan; zhu, Xinglong; Yang, Lijing; Li, Bernard Qiong; Cho, Kailynn; Song, Zhenlun; Zhang, Yi
Abstract: Bimodal coarse-grained (BCG ) and unimodal ultrafine-grained (UUFG ) Zn-0.5Mn alloys were prepared in this paper, and the mean grain sizes under two different conditions were approximately 1.20 and 0.40 µm, respectively. The remarkable difference in the microstructure of BCG and UUFG led to a substantial increase in ductility, and the latter's maximum elongation-to-failure reached 266.2% ± 8.3% at room temperature (RT). Analysis of the microstructural features of the broken tensile sample longitudinal section showed that different from BCG, the grain size of UUFG sample decreased gradually from distal to proximal fracture. It also showed a marked grain elongation (growth) because ultrafine grains rotate during plastic deformation and could coalesce along the directions of shear, creating larger paths for dislocation movement, which may be the most important facts of obtaining RT superplasticity. The MnZn13 particles in UUFG had enhanced grain refining efficiency during uniaxial tension compared with those in BCG . Thus, UUFG microstructure remarkably increased the plasticity of Zn-0.5Mn alloy while the suitable temperature region for superplastic deformation was low, which is important for practical application. The investigation of short-term biocompatibility in vivo revealed that the bone biocompatibility of UUFG was quite good, which could induce early osteoid tissue deposition, and no distinguishable injury to the structure/function of the liver and the kidney was found. Graphical Abstract: ga1